A room with a view - Forster, E. M. (Edward Morgan), 1879-1970. (London : Penguin Books, 2001)
Lucy Honeychurch is at war with the snobbery of her class and her desires when she finds herself attracted to someone socially unsuitable.
First published in Great Britain by Edward Arnold 1908.
Adult.
Adult
Keywords: British -- Travel -- Italy -- Florence -- Fiction; Young women -- England -- Fiction; British -- Fiction; Humorous fiction; Young women -- England -- Fiction; Florence (Italy) -- Fiction; Florence (Italy) -- Fiction; Humorous stories